Mandibular Distraction Osteogenesis in the Micrognathic Neonate: A Review for Neonatologists and Pediatricians - Paul Hong; Michael Bezuhly (Elsevier, 2013)
In the past, severe neonatal upper airway obstruction secondary to micrognathia was managed with a tracheostomy. Although effective, tracheostomy can cause many short-term and long-term complications. More recently, mandibular distraction osteogenesis (MDO) has become a well-accepted surgical option in treating micrognathic newborns. Overall, MDO has been reported to be an effective intervention in alleviating the micrognathia-associated airway compromise. Furthermore, it seems to be well tolerated and has supplanted the need for tracheostomy in many patients. Neonatologists and pediatricians commonly care for these children, and therefore an up-to-date clinical narrative review regarding MDO is presented to increase the awareness of this relatively new surgical option.